2018
DOI: 10.1002/smll.201704077
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid/Phospholipid Blended Membranes: A Potential Intermediate State in Protocellular Evolution

Abstract: Prior to the evolution of membrane proteins, intrinsic membrane stability and permeability to polar solutes are essential features of a primitive cell membrane. These features are difficult to achieve simultaneously in model protocells made of either pure fatty acid or phospholipid membranes, raising the intriguing question of how the transition from fatty acid to phospholipid membranes might have occurred while continuously supporting encapsulated reactions required for genomic replication. Here, the properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 30 publications
6
102
0
Order By: Relevance
“…Furthermore, we can rule out that fatty acids themselves mediate or trigger growth without the need of membrane tension, as previous studies have clearly shown that hybrid vesicles are able to grow only in presence of pure fatty acid vesicles, and not in presence of hybrid vesicles . This observation is further strengthened by a recent study, where the surface area of hybrid vesicles with 50% or higher phospholipid content was shown to remain completely constant in presence of Mg 2+ , proving the ability of phospholipids to efficiently retain the fatty acids in the hybrid membranes …”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, we can rule out that fatty acids themselves mediate or trigger growth without the need of membrane tension, as previous studies have clearly shown that hybrid vesicles are able to grow only in presence of pure fatty acid vesicles, and not in presence of hybrid vesicles . This observation is further strengthened by a recent study, where the surface area of hybrid vesicles with 50% or higher phospholipid content was shown to remain completely constant in presence of Mg 2+ , proving the ability of phospholipids to efficiently retain the fatty acids in the hybrid membranes …”
Section: Resultsmentioning
confidence: 61%
“…Alternatively, fatty acid vesicles are studied as a model system for protocells that are hypothesized to have been involved in the emergence of life on the early earth. Bridging the gap between the protocells and the modern cells, hybrid vesicles, which are composed of both lipids and fatty acids, have been studied as yet another model system . These hybrid systems are also potentially interesting scaffolds for synthetic cells as they exhibit a valuable combination of features, in particular an enhanced stability against Mg 2+ , while retaining permeability to small charged molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of environments compatible artificial lipid bilayers which possess a robust structure are highly significant for artificial cells development. [201] Castell and co-workers reported the fabrication of lipid bilayers in the hydrogel shell by microfluidics ( Figure 8B). [202] In this work, the structure of artificial cells can be adjusted by controlling the number of internal droplets and compositions.…”
Section: Synthesizing Artificial Cell Membranes By Microfluidicsmentioning
confidence: 99%
“…Vesicle structures can form spontaneously from fatty acids, as first reportedi n1 973, [44] and such membranes mightay have surrounded the first cells. [47] Well-sealed, stable membranes can also be formed from block copolymers, [48] but the functional incorporation of integral membranep roteins is challenging, especially when the proteins requirespecific lipids as cofactors. Fatty acid-phospholipid blended membranes display increased stabilityb ut still maintain permeability for small (charged) solutes.…”
Section: Building Blocks For Membranesmentioning
confidence: 99%
“…They might have formed an intermediate in protocellulare volution, which allowed membrane passage withouttransporters. [47] Well-sealed, stable membranes can also be formed from block copolymers, [48] but the functional incorporation of integral membranep roteins is challenging, especially when the proteins requirespecific lipids as cofactors. The majority of successfulr econstitutions in non-native amphiphilic membranes involver elativelys table membrane pores or channels that do not undergo large conformational changes in the membrane.…”
Section: Building Blocks For Membranesmentioning
confidence: 99%